2005
DOI: 10.1080/09593330.2001.9619503
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Mill Wastewater Purification by Combination of Coagulation- Flocculation and Biological Treatments

Abstract: In order to define an efficient pre-treatment of Olive Oil Mill Wastewater (OOMW) to overcome major obstacles to biological treatment, various organic and mineral coagulants have been tested. In particular, the application of quicklime until a pH around 12 - 12.4 was reached, allowed the reduction of almost 37% of the initial COD, and approximately 88% and 71% of the colour and phenolic content of the waste. Hence, further biological treatments with an adapted aerobic consortium (AC) and a white rot fungus (WR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 14 publications
6
25
0
2
Order By: Relevance
“…Fe(III) at 1000 mg/L led to about 14%, 10% and 50% TSS, TP and COD reduction, respectively; these values were reduced to 5.6%, 7% and 10%, respectively, increasing Fe(III) concentration to 2000 mg/L, while further increase to 3000 mg/L gave no separation (data not shown). Jaouani et al [6] who studied OME treatment by Fe(III) coagulation reported the existence of an optimum coagulant concentration at which treatment efficiency was maximised; at concentrations greater than the optimum one, separation was suppressed and this was attributed to colloids being restabilised. PAC at a concentration of 1000 mg/L gave moderate TSS removal of about 60%, while COD decrease did not exceed 10%.…”
Section: Screening Of Various Coagulantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Fe(III) at 1000 mg/L led to about 14%, 10% and 50% TSS, TP and COD reduction, respectively; these values were reduced to 5.6%, 7% and 10%, respectively, increasing Fe(III) concentration to 2000 mg/L, while further increase to 3000 mg/L gave no separation (data not shown). Jaouani et al [6] who studied OME treatment by Fe(III) coagulation reported the existence of an optimum coagulant concentration at which treatment efficiency was maximised; at concentrations greater than the optimum one, separation was suppressed and this was attributed to colloids being restabilised. PAC at a concentration of 1000 mg/L gave moderate TSS removal of about 60%, while COD decrease did not exceed 10%.…”
Section: Screening Of Various Coagulantsmentioning
confidence: 97%
“…Coagulation with materials such as lime, alum, ferric chloride and ferrous sulphate has also been employed in OME treatment. Jaouani et al [6] recently demonstrated a two-stage process comprising aerobic degradation followed by lime coagulation, while Beccari et al [7] proposed a process comprising OME pre-treatment by means of lime coagulation and adsorption on bentonite followed by anaerobic digestion; they reported that pre-treatment was capable of enhancing considerably the anaerobic treatability of the original effluent. The effect of several OME pre-treatments such as lime or ammonium iron sulphate coagulation, resin adsorption and H 2 O 2 oxidation on subsequent anaerobic degradability was investigated by Zouari [8] who found that the pre-treated effluent was always more readily amenable to biodegradation than the original un-treated effluent.…”
Section: Introductionmentioning
confidence: 98%
“…Activated sludge plants and other conventional biological treatment are barely proficient in removing such pollutants. A sequence of various physicochemical and biological treatments is thus commonly required to treat efficiently OOMW (Ranalli 1991; Khoufi et al 2004;Jaouani et al 2005). Microorganisms, in particular white rot fungi (WRF), were proposed as possible candidates for the biological step of OOMW treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Les procĂ©dĂ©s physico-chimiques : coagulation-floculation (KISSI, 2002;JAOUANI et al, 2005;SARIKA et al, 2005), neutralisation avec la chaux (AKTAS et al, 2001;FLOURI et al, 1996;KHOUFI et al, 2000;RANNALI, 1991b;), Ă©lectro-coagulation (INAN et al, 2004), adsorption sur charbon actif (ERSOY et al, 1998;MORINO-CASTILLO et al, 2001) et adsorption sur l'argile (AL-MALLAH et al, 2000AZZOUZI, 1997). …”
Section: Introductionunclassified